2017
DOI: 10.1007/s00586-017-5172-x
|View full text |Cite
|
Sign up to set email alerts
|

Proximal junctional kyphosis in adult scoliosis: comparison of four radiological predictor models

Abstract: Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 25 publications
7
44
1
Order By: Relevance
“…We have found an incidence of 18.4% of PJK in this population similar to that reported in the literature [17]. In a recent evaluation of a large database of adult deformity patients, restoring the sagittal apex of the lordosis and its effects on the incidence of PJK was analyzed [13]. When postoperative sagittal apex of the lumbar curve was identical to the theoretical apex, PJK occurred in 13.5% of the cases, whereas it occurred in 41.4% in cases where the theoretical and actual apex were different (p = 0.01) with an OR = 4.6.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We have found an incidence of 18.4% of PJK in this population similar to that reported in the literature [17]. In a recent evaluation of a large database of adult deformity patients, restoring the sagittal apex of the lordosis and its effects on the incidence of PJK was analyzed [13]. When postoperative sagittal apex of the lumbar curve was identical to the theoretical apex, PJK occurred in 13.5% of the cases, whereas it occurred in 41.4% in cases where the theoretical and actual apex were different (p = 0.01) with an OR = 4.6.…”
Section: Discussionsupporting
confidence: 85%
“…In the recent available medical literature, there are no clear guidelines for ASD correction as PI-LL formula yielded unacceptably high rates of mechanical complications and the updated age specific goals are yet to yield definitive guidelines [12]. Moreover, it has recently been published that restoring the apex of the lordosis to the levels corresponding to the Roussouly classification would reduce the risk of PJK by a ratio of 4.6 [13]. Based on the fact that identification of the correspondence between pelvic incidence and spinal degenerative shape would allow recognizing the original "normal" shape, the proposed algorithm is to restore the low-pelvic-incidence patients to type 1 or type 2 while restoring higher-pelvic-incidence patients to type 3 and type 4.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the occurrences of PJK were very high when apexes of sagittal lordosis were not at their theoretical position compared to when they're positioned at their theoretical position. These findings are similar to what has been reported in the literature by other scholars (18).…”
Section: Formulasupporting
confidence: 93%
“…Yagi et al (2) in their retrospective review of 157 cases, they found that more than 80% of patient with non-ideal global sagittal alignment (GSA> 45 0 ) developed PJK, and the OR for these patients was 29. Sebaaly et al (18) in their retrospective study of 250 cases of adult idiopathic scoliosis from a multicentric database, found that GSA >45 0 was associated with the occurrences of PJK, with OR 1.7. in this study we also found that GSA> 45 0 is highly associated with occurrences of PJK, with OR 2.5. This might be explained by the reason that increased GSA results in the positive (SVA) and increases the stress for the proximal and distal junctions of instrumentation that lead to the development of PJK (19).…”
Section: Formulamentioning
confidence: 99%
“…Many risk factors have been identified to be associated with the development of PJK� however, development of prediction models is still in early stages with individual precise prediction remaining difficult so far [30].…”
Section: Discussionmentioning
confidence: 99%